Pengaruh Harga, Lokasi, Fasilitas, Dan Kualitas Informasi Terhadap Keputusan Pemilihan Indekos Pada Mahasiswa Universitas PGRI Madiun - Jasmine Putri Anjani; Wikanso Wikanso; Dwi Nila Andriani (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
This study aims to: (1) To determine the effect of price on boarding house selection decisions for PGRI Madiun University students, (2) To determine the effect of facilities on boarding house selection decisions for PGRI Madiun University students, (3) To determine the effect of location on boarding house selection decisions for PGRI Madiun University students, (4) To determine the effect of information quality on boarding house selection decisions for PGRI Madiun University students, (5) To determine the effect of price, facilities, location, and quality of information on boarding house selection decisions for PGRI Madiun University students. . This research method is included in quantitative research with the type of associative causal research. As for data collection techniques using questionnaires and documentation. The sampling technique used is random sampling. The population in this study were PGRI Madiun University students who used boarding houses. The sample of this research is 152 respondents. The results showed that variable X1 had a significant effect of 14.2% partially, variable X2 had a significant effect of 17.6% partially, variable X3 had a significant effect of 14.7% partially, and variable X4 had a significant effect of 22.7% partially. While the rest is influenced by other factors not explained in this study.